Photon’s Mass (m) is a Function (f) of its Energy(E): m = f (E) (A Possible New Postulate) - Puccini, Antonio (European Journal of Applied Sciences, 2026)
Analyzing the numerous effects induced by electromagnetic radiations (EMRs), such as the photo-electric effect, or the Compton effect, in which the photon(P) behaves physically like a microscopic billiard pellet, with mechanical effects superimposable on those performed by massive particles, we suspect that the momentum(p) of P transports, with its motion, also a dynamic-mass, likely in the form of mass-energy density (however undetectable during motion: the Complementarity Principle prohibits it). Besides, as Pacini reminds us, ‘motion itself is mass’. Applying the de Broglie formula (p=h/λ) to the EMRs, it emerges that the momentum (p) of an optical P corresponds to 1.325∙10-22 [g∙cm/s], i.e. values over 100,000 times greater than the rest mass of the electron. Planck itself expressed in erg∙sec, that is, in grams ∙cm2/s, the value of the well-known ‘natural constant’, h, which represents the physical, concrete, real heart, of the ‘quantum of EMR’, or Planck's grain: how to say P. Thus, the parameter h is indicated in grams, values therefore likely referable to a mass density, quantitatively invariant, even during motion, unlike energy, which instead varies with the wavelength (λ) of the P considered. This is what is correctly found in the work, comparing the values of the Ps momenta of different λ, thus confirming that the probable mass density conveyed by Ps is a function of their energies.